Atezolizumab and bevacizumab-induced encephalitis in advanced hepatocellular carcinoma: Case report and literature review. Issue 24 (18th June 2021) - Özdirik, Burcin; Jost-Brinkmann, Fabian; Savic, Lynn Jeanette; Mohr, Raphael; Tacke, Frank; Ploner, Christoph J.; Roderburg, Christoph; Müller, Tobias
Abstract: Introduction: On the basis of the results of the IMBRAVE-150 trial, the combination of atezolizumab, a programmed cell death ligand 1 (PD-L1) antibody, as well as bevacizumab, a vascular endothelial growth factor (VEGF) antibody, represents a promising novel first-line therapy in patients with advanced hepatocellular carcinoma (HCC). Despite favorable safety data, serious adverse events have been described. However, central nervous system complications such as encephalitis have rarely been reported. We present the case of a 70-year-old woman with hepatitis C virus (HCV)-related liver cirrhosis and advanced HCC who developed severe encephalitis after only one cycle of atezolizumab/bevacizumab. Patient concerns: Ten days after administration, the patient presented with confusion, somnolence, and emesis. Within a few days, the patient's condition deteriorated, and mechanical ventilation became necessary. Diagnosis: Cerebrospinal fluid (CSF) analysis showed increased cell count and elevated protein values. Further work-up revealed no signs of an infectious, paraneoplastic, or other autoimmune cause. Intervention: Suspecting an atezolizumab/bevacizumab-related encephalitis, we initiated a high-dose steroid pulse therapy as well as repeated plasmapheresis, which resulted in clinical improvement and remission of CSF abnormalities. Outcome: Despite successful weaning and transfer to a rehabilitation ward, the patient died of progressive liver cancer 76 days after initial treatment with atezolizumab/bevacizumab, showing no response. Conclusion: This case illustrates that rapid immunosuppressive treatment with prednisolone can result in remission even of severe encephalitis. We discuss this case in the context of available literature and previously reported cases of atezolizumab-induced encephalitis in different tumor entities, highlighting the diagnostic challenges in oncologic patients treated with immune checkpoint-inhibitors.